Guest

why is vectorA-vectorB=(A*A)+(B*B)-2AB cos θ?But vectorA-vectorB=(A*A)+(B*B)+2AB cos θ.Wheat is the reason for the change in equation?

why is vectorA-vectorB=(A*A)+(B*B)-2AB cosθ?But vectorA-vectorB=(A*A)+(B*B)+2AB cosθ.Wheat is the reason for the change in equation?

Grade:11

1 Answers

Yogendra Kumar
askIITians Faculty 122 Points
4 months ago
There is a mistake in the question.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free